Identifying programmatic gaps: inequities in harm reduction service utilization among male and female drug users in Dar es Salaam, Tanzania. - Lambdin, Barrot H; Bruce, R Douglas; Chang, Olivia; Nyandindi, Cassian; Sabuni, Norman; Zamudio-Haas, Sophia; McCurdy, Sheryl; Masao, Frank; Ivo, Yovin; Msami, Amani; Ubuguy, Omar; Mbwambo, Jessie (PloS one, 2013)
Current estimates suggest an HIV prevalence of 42% among people who inject drugs (PWIDs) in Dar es Salaam, while HIV prevalence is estimated to be 8.8% among the general population in the city. To address the HIV epidemic in this population, the government of Tanzania began establishing HIV prevention, treatment and care services including outreach and medication assisted treatment (MAT) for PWIDs in 2010. We assessed gender inequities in utilization of outreach and MAT services and evaluated differences in HIV risk behaviors between female and male PWIDs.
Keywords: Adult; Community-Institutional Relations; Drug Users; Female; Harm Reduction; Health Services Accessibility; HIV Infections; Humans; Male; Middle Aged; Risk-Taking; Sex Factors; Socioeconomic Factors; Substance-Related Disorders; Tanzania